2021
DOI: 10.3389/fpsyg.2021.685351
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Perceived Risk and Negative Emotions on the Service Recovery Effect for Online Travel Agencies: The Moderating Role of Corporate Reputation

Abstract: This study explores the impact mechanism of perceived risk and negative emotions on the service recovery effect of an online travel agency (OTA) through a scenario experiment. The results show that: perceived risk has positive and negative impacts on negative emotions and service recovery satisfaction, negative emotions have a negative impact on service recovery satisfaction, and corporate reputation plays a positive moderating role in the relationship between perceived risk and service recovery satisfaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…In a previous study, the researchers claimed that the online shopping is a new concept that could subvert over the position of traditional shopping and get rid of the limitation of services provided by humans. Some researchers also put forward a similar opinion that the online shopping based on machinery and procedures did not have the ability to exchange emotion with consumers, so that consumers would not have demands and expectation emotionally, which could create a fair competitive channel because the consumer would only focus on the quality of products (see also Wei, 2021 ). This claim seems reasonable according to the background of era, but it has been denied at present.…”
Section: The Conceptual Analysismentioning
confidence: 99%
“…In a previous study, the researchers claimed that the online shopping is a new concept that could subvert over the position of traditional shopping and get rid of the limitation of services provided by humans. Some researchers also put forward a similar opinion that the online shopping based on machinery and procedures did not have the ability to exchange emotion with consumers, so that consumers would not have demands and expectation emotionally, which could create a fair competitive channel because the consumer would only focus on the quality of products (see also Wei, 2021 ). This claim seems reasonable according to the background of era, but it has been denied at present.…”
Section: The Conceptual Analysismentioning
confidence: 99%
“…Third, the significant moderating effects of the emotional attachment on the correlations between distributive and procedural justice on recovery satisfaction imply that the higher the emotional attachment, the stronger the positive correlations between distributive and procedural justice on recovery satisfaction. If the emotional attachment is low, it will be challenging for e-retailers to earn a high level of recovery satisfaction even with service recovery efforts ( Wei, 2021 ). Therefore, e-retailers should prioritize increasing customers’ emotional attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al (2022) provided a close relationship between risk perception and knowledge based on multiple linear regression models. Wei (2021) studied the impact of interest development and information acceptance on public perceptions of risk in different sectors, finding that mastery of risk-related knowledge has a detrimental impact on public perceptions. They confirmed the "knowledge weakening hypothesis of public risk perception" and found that risk knowledge negatively impacted risk perception using typology methods.…”
Section: Impact Of Risk Knowledge On Risk Perceptionmentioning
confidence: 99%